Inhibition characteristics of biofilm structure of Staphylococcus aureus - Zhang, Liping; Jin, Mingxiao; Sun, Meng (Cellular and Molecular Biology, 2020)
Different extracts have different effects on the biofilm structure of Staphylococcus aureus, and the biofilm structure of Staphylococcus aureus will produce different inhibition reactions. In this study, different experimental reagent extracts were used to analyze the inhibition characteristics of Staphylococcus aureus biofilm structure. The inhibition characteristics of bacterial biofilm structure were obtained by using the same bacteria species and the same experimental environment. The results showed that the chloroform extract had a good inhibitory effect on the biofilm structure, which could effectively inhibit the formation of biofilm; the acetic acid extract had an impact on the formation of biofilm, which was destructive to the biofilm; the petroleum ether extract had no effect on the formation of biofilm, that is, it had no inhibitory effect.